2022
DOI: 10.1186/s12875-022-01683-1
|View full text |Cite
|
Sign up to set email alerts
|

An integrated primary care-based programme of PRE-Pregnancy cARE to improve pregnancy outcomes in women with type 2 Diabetes (The PREPARED study): protocol for a multi-method study of implementation, system adaptation and performance

Abstract: Background The number of women of childbearing age with Type 2 diabetes(T2DM) is increasing, and they now account for > 50% of pregnancies in women with pre-existing diabetes. Diabetes pregnancies without adequate pre-pregnancy care have higher risk for poor outcomes (miscarriages, birth-defects, stillbirths) and are associated with increased complications (caesarean deliveries, macrosomic babies, neonatal intensive-care admissions). The risks and costs of these pregnancies can be reduced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Some studies have pointed out that nursing intervention can effectively control the blood glucose of children with type 2 diabetes and improve their compliance with treatment, so as to delay the progress of the disease and improve patients' life experience [15][16][17], but there is still a lack of relevant medical evidence. Therefore, we systematically evaluated the effect of nursing intervention in children with type 2 diabetes by retrieving relevant literature and applying meta-analysis method, so as to provide medical evidence for the clinical promotion and application of nursing intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have pointed out that nursing intervention can effectively control the blood glucose of children with type 2 diabetes and improve their compliance with treatment, so as to delay the progress of the disease and improve patients' life experience [15][16][17], but there is still a lack of relevant medical evidence. Therefore, we systematically evaluated the effect of nursing intervention in children with type 2 diabetes by retrieving relevant literature and applying meta-analysis method, so as to provide medical evidence for the clinical promotion and application of nursing intervention.…”
Section: Introductionmentioning
confidence: 99%
“…These studies both aim to integrate pre‐pregnancy care for women with type 2 diabetes into primary care. The proposed interventions components for these studies include: modified electronic health record technology to promote pre‐pregnancy care discussions 28,29 ; health professional education 28 ; education resources for women with type 2 diabetes 28,29 ; and text message prompts to promote health behaviours 29 . Both of these studies address many of the limitations identified in the previous studies as they are theoretically grounded and focused on primary care settings.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, to the authors knowledge, no studies assessing the effectiveness of the PADI app have yet been published. There are two ongoing studies of relevance, with one based in the UK (the PREPARED study), 28 while the other is based in the US. 29 These studies both aim to integrate pre-pregnancy care for women with type 2 diabetes into primary care.…”
Section: Review Limitationsmentioning
confidence: 99%